Teaching Piano in Colleges and Universities Based on Cross-Cultural Music Education - Wei, Zhe Yuan (Música Hodie, 2023)
The paper primarily analyzes aspects of college and university piano instruction based on cross-cultural music education. The paper established the elements that are most important for students to learn. 32 percent of students believe that implementing best practices would make a significant difference in the learning effectiveness. The survey revealed that only 5% of students have more than one month of full-time online learning experience. The findings suggested that 29% of the respondents developed creative thinking skills, and 26% of the respondents gained technical knowledge that contributed to strong improvisation skills. Data on productivity revealed that six out of eight study groups achieved a high level, and only group 3 (college) scored 19.6%, which is due to the lack of good grades among most students.